Analisis Kompetensi Pedagogik dan Pengembangan Pembelajaran Guru SD Negeri 041 Tarakan - Sumiarsi, Ninik (Jurnal Kebijakan dan Pengembangan Pendidikan, 2015)
Analisis Kompetensi Pedagogik dan Pengembangan PembelajaranGuru SD Negeri 041 TarakanNinik SumiarsiDinas PendidikanTarakanEmail:ninik_s@gmail.comAbstract:This research objective was to know pedagogic competency owned by teachers and also understand learning development at public elementary school 041 Tarakan. This research used qualitative-quantitaive method where the researcher attempted to analyze data through the source of primary data which were structured interview result with teachers at public elementary school 041 tarakan. It was also completed with the secondary data source which was information collected based on respondents’ answer towards questionnaire, including documentation data and observation transcript. The result showed that pedagogic competencies owned by teacher Public Elementary School 041 Tarakan had been in line with the regulation of National Education Minister No. 16 year 2007, but it still needed several improvements and enhancements. Furthermore, learning development in Public Elementary School 041 Tarakan is very necessary to complete every weakness. The form of development strategy which can be carried out was bottom-up developmentKeywords: competency, pedagogic, teacher, development, learningAbstrak:Penelitian ini bertujuan untuk mengetahui kompetensi pedagogik yang dimiliki guru serta memahami pengembangan pembelajaran di Sekolah Dasar Negeri 041 Tarakan. Penelitian ini menggunakan metode kualitatif-kuantitatif dimana peneliti berupaya mengupas data penelitian melalui sumber data primer berupa hasil wawancara secara terstruktur dengan guru di SDN 041 Tarakan, dilengkapi pula dengan sumber data sekunder berupa informasi yang dikumpulkan berdasarkan jawaban responden terhadap kuisioner, termasuk pula data dokumentasi dan transkrif observasi. Hasil penelitian menunjukkan, bahwa kompetensi kompetensi pedagogik yang dimiliki Guru SDN 041 Tarakan sudah sejalan dengan Peraturan Menteri Pendidikan Nasional Nomor 16 Tahun 2007, namun perlu ada beberapa perbaikan atau peningkatan. Selanjutnya pengembangan pembelajaran di SDN 041 Tarakan sangat diperlukan guna melengkapi segala kekurangan yang ada. Bentuk strategi pengembangan yang dapat dilakukan adalah pengembangan yang bersifat bottom-up.Kata kunci: kompetensi, pedagogik, guru, pengembangan, pembelajaran.